2013
DOI: 10.2139/ssrn.2377341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Decade of Mobile Termination Rate Regulation

Abstract: We re-consider the impact that regulation of call termination on mobile phones has had on mobile customers' bills. Using a large panel covering 27 countries, we find that the "waterbed" phenomenon, initially observed until early 2006, becomes insignificant on average over the 10-year period, 2002-2011. We argue that this is related to the changing nature of the industry, whereby mobile-to-mobile traffic now plays a much bigger role compared to fixed-to-mobile calls in earlier periods. Over the same decade, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Thus, after FMS has gone on for a sufficiently long time mobile carriers should on balance no longer oppose termination charge reductions. While my conjecture is that for the EC the charge reduction to pure LRIC is only a stepping stone for a move to B&K, Genakos and Valletti (2014) see pure LRIC as a natural end point for termination charge reductions.…”
Section: Downward Trend In Termination Chargesmentioning
confidence: 78%
See 2 more Smart Citations
“…Thus, after FMS has gone on for a sufficiently long time mobile carriers should on balance no longer oppose termination charge reductions. While my conjecture is that for the EC the charge reduction to pure LRIC is only a stepping stone for a move to B&K, Genakos and Valletti (2014) see pure LRIC as a natural end point for termination charge reductions.…”
Section: Downward Trend In Termination Chargesmentioning
confidence: 78%
“…Building on theoretical models by Armstrong and Wright (2009) The waterbed effect is usually seen as a cushion against profit reductions from termination charge reductions. However, Genakos and Valletti (2014) show that profits on average are not significantly changed as a result of termination charge reductions after 2006 (i.e., without waterbed effect). Thus, after FMS has gone on for a sufficiently long time mobile carriers should on balance no longer oppose termination charge reductions.…”
Section: Downward Trend In Termination Chargesmentioning
confidence: 88%
See 1 more Smart Citation
“…For some recent analyses, see e.g. Genakos and Valletti (2015), Armstrong andWright (2009), Harbord andHoernig (2015) and Hurkens and Lopez (2014). In our paper we have disregarded this question altogether and focused on cost-based termination rates in our main proofs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Genakos and Valletti (2011) found that call termination rate reductions increased retail prices as a result of a 'waterbed effect'. The same authors more recently found that this 'waterbed effect' had disappeared over time (Genakos & Valletti, 2014). However, Kongaut and Bohlin (2012) found that call termination rate reductions have led to decreases in retail prices, while Veronese and Pensendorfer (2009) found no relationship between MTR reductions and retail prices.…”
Section: Theoretical and Empirical Research On The Impact Of Call Termentioning
confidence: 99%